Uso de analogias como recurso didático na disciplina de transmissão de calor - Matelli, José Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The use of analogies as a didactic resource in the discipline of heat transfer is discussed in this thesis. The application of analogies in teaching is reviewed in the literature, so that a theoretical framework that justifies the use of analogies can be established. Thus, it is proposed that the analogy can be interpreted as a Vigotski's symbolic mediation. Uses of analogies either adapted or developed in the classroom by the author of this thesis are presented. The impressions of the author about the students' receptivity to the resource are discussed, as well as some cases of interaction with the students are presented

Disserta-se nessa tese sobre o uso de analogias como recurso didático na disciplina de transmissão de calor. A aplicação de analogias no ensino é revisada na literatura, de modo que se estabeleça um referencial teórico que justifique este uso. Assim, propõe-se que a analogia possa ser interpretada como um mediador simbólico de Vigotski. Usos de analogias adaptadas ou desenvolvidas em sala de aula pelo autor da presente tese são apresentados. As impressões do autor acerca da receptividade dos alunos ao recurso são discutidas, bem como alguns casos de interação com os alunos são apresentados
Use of analogies as didactic resource in the discipline of heat transmission
Keywords: Heat transfer; Teaching; Analogy; Didatic resource; Calor - Transmissão; Analogia; Ensino; Material didático; Heat Transmission